The Utilization of Fallen Fruits as Raw Materials for Producing Liquid Organic Fertilizer in Bogor Botanic Gardens - Iin Pertiwi A Husaini; Irfan Martiansyah; Angga Yudaputra; Riki Ruhimat; Enggal Primananda; Lydia Natalia Endewip; Winda Ika Susanti (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2022)
AbstrakBogor Botanic Garden is an area designated to conserve and protect many species of plants from Indonesia and other countries as well. Most plant collections belonged to plants that continuously producing fruits. Many of fallen fruits produced by different plant species still remained optimally unmanaged and unutilized. The objective of this study was to increase the value of fallen fruits by utilizing it as raw materials for producing organic liquid fertilizer (POC). The first step of this study was conducted by collecting data about the species of fruiting plants. Liquid organic fertilizer was produced using a semi-anaerobic fermentation system with adding an effective microorganism 4 (EM 4). The results showed that there were 19 trees from 15 species such as Parmentiera cereifera, Ficus racemosa, F. fistulosa, and Dillenia indica. The fertilizers are made with a variety of supporting materials to produce liquid organic fertilizer (type A) and liquid organic fertilizer (type B). The temperature and pH had the similar value pattern during the fermentation process. Liquid organic fertilizer (type B) has a C/N ratio of 37.65, higher than liquid organic fertilizer (type A) which is 27.23. In addition, the C-organic liquid organic fertilizers (type B) was higher than liquid organic fertilizers (type A). The C-organic and N, P, and K contents have not reached the minimum technical standard for organic fertilizers that regulated on Decree of the Minister of Agriculture Number 261/KPTS/SR.310/M/4/2019. Eventually, the optimization attempts to increase the C-organic and N, P, and K contents on liquid organic fertilizer will be subsequently required.Abstract Kebun Raya Bogor merupakan kawasan konservasi tumbuhan yang memiliki koleksi berbagai macam jenis tumbuhan yang berasal dari Indonesia maupun dari luar negeri. Sebagian besar tumbuhan merupakan tumbuhan yang menghasilkan buah setiap tahunnya. Selama ini buah dalam jumlah banyak yang jatuh dari pohonnya belum termanfaatkan secara optimal. Tujuan dari penelitian ini adalah untuk meningkatkan nilai tambah limbah buah tersebut sebagai bahan dasar untuk pembuatan pupuk organik cair (POC). Studi awal dilakukan pendataan jenis tumbuhan yang berpotensi menghasilkan buah non-edible. Pembuatan POC dilakukan dengan sistem fermentasi semi-anaerobik menggunakan aktivator Effective Microorganism 4 (EM4). Hasil penelitian menunjukkan terdapat 19 pohon dari 15 jenis tumbuhan di antaranya Parmentiera cereifera, Ficus racemosa, F. fistulosa, dan Dillenia indica. Pupuk organik cair dibuat dengan variasi bahan pendukung yang berbeda menghasilkan POC A dan POC B. Pola perubahan suhu dan pH pada saat proses fermentasi relatif sama untuk kedua jenis POC. POC B memiliki rasio C/N sebesar 37,65 lebih tinggi dibandingkan dengan POC A yang hanya sebesar 27,23. Selain itu, konsentrasi Corganik POC B yang lebih tinggi daripada POC A. Nilai C-organik dan N, P, K diketahui belum mencapai standar teknis minimal pupuk organik berdasarkan SK Menteri Pertanian Nomor 261/KPTS/SR.310/M/4/2019 sehingga diperlukan optimalisasi fermentasi lebih lanjut.